Interactions between colliding oil drops coated with non-ionic surfactant determined using optical tweezers. (16th January 2019) - Chen, An; Li, Shao-Wei; Jing, Dian; Xu, Jian-Hong
Graphical abstract: Highlights: This work provides novel observations of the charging behavior at O/W interface. The tetradecane drops coated non-ionic surfactant FS-30 are negatively charged. The effects of various salt cases on the interactions were studied systematically. Abstract: Non-ionic surfactants are widely used in many industrial applications such as detergents, oil recovery, and mineral flotation techniques. Non-ionic surfactants readily adsorb onto the oil-water interface, although they cannot dissociate in solutions like ionic surfactants can. Nonetheless, the electrostatic double-layer (EDL) repulsive force between oil drops coated with the non-ionic surfactant can still provide stability against coalescence. In this work, the interaction forces between two tetradecane drops with diameter of 6.5 µm were measured in the presence of the non-ionic fluorocarbon-based surfactant FS-30 in various salt solutions using optical tweezers. The measured force curves were consistent with the presence of a surface charge, even though the surfactant was non-ionic in nature. The results clearly show that the EDL repulsive force is gradually screened with increasing salt concentration. It was also found that the EDL repulsive force was significantly screened in the divalent cation salt solutions (Ca 2+, Ba 2+ ) in comparison to in the monovalent cation salt solutions (Na + ). In addition, the absolute value of the measured zeta potential ( − ξ ) of emulsified tetradecane drops gradually decreased with increasing FS-30 concentration. In all experimental processes, the emulsified tetradecane drops coated with FS-30 were stable against coalescence. These findings have significant implications for the stability of emulsions used in the food, cosmetic, and detergent industries.